2022
DOI: 10.1155/2022/5879137
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, and Their Variations as a Basis for a Prediction Model in Advanced NSCLC Patients Receiving Anlotinib

Abstract: Background. A phase III randomized multicenter trial (ALTER0303) reported anlotinib to be significantly beneficial to patient survival. An array of inflammatory biomarkers, such as neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR), are associated with the response to treatment in numerous types of cancer. However, we found few studies investigating the predictive value of NLR or PLR in advanced NSCLC treatment with anlotinib. Thus, our objective was to examine the relationship between NLR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Recently, three retrospective studies about SCLC treatment with anlotinib had tried to select some ways to identify those benefit patients, which indicated that the response to first‐line treatment, 22 prognostic nutritional indexes, 11 and tumor cavitation 9 could predict survival independently, yet all through relatively simple means. Our team once established a system of risk scores by different combinations of multiple inflammatory indicators in NSCLC, which was capable of predicting the best population for anlotinib treatment 7 . Therefore, this study was focused on developing a prognostic scoring system in SCLC that included NLR, PLR, and LMR and successfully selecting the dominant population, which was bound to be more comprehensive than a single prognostic factor as previously described.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, three retrospective studies about SCLC treatment with anlotinib had tried to select some ways to identify those benefit patients, which indicated that the response to first‐line treatment, 22 prognostic nutritional indexes, 11 and tumor cavitation 9 could predict survival independently, yet all through relatively simple means. Our team once established a system of risk scores by different combinations of multiple inflammatory indicators in NSCLC, which was capable of predicting the best population for anlotinib treatment 7 . Therefore, this study was focused on developing a prognostic scoring system in SCLC that included NLR, PLR, and LMR and successfully selecting the dominant population, which was bound to be more comprehensive than a single prognostic factor as previously described.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Although we found similar results in this study but did not share the same cut‐off value, which is 240.56 in SCLC and 205.63 in NSCLC, the conclusion from our previous study about NSCLC patients receiving anlotinib indicated that high pre‐PLR was related to poor outcome. 7 This phenomenon revealed the existence of different tumors with different cutoff values and the possibility of the difference being caused by insufficient sample capacity. In order to improve the predictive ability of the anlotinib drug, we set up an inflammatory‐based prognostic score system according to the independent prognostic factors from our research (post‐NLR elevation, pre‐PLR > 240.56, and pre‐LMR ≤1.61).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the neutrophil-to-lymphocyte ratio (NLR), [ 5 ] lymphocyte-to-monocyte ratio (LMR) [ 6 ] and platelet-to-lymphocyte ratio (PLR) [ 7 ] have been found to be independent predictors of prognosis in various benign and malignant conditions [ 8 , 9 , 10 , 11 ]. Moreover, NLR, LMR and PLR were reported to be related to the outcome of intensive care unit (ICU) patients, because of their rapid response to systemic inflammation and stress [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%